Case Report: Cabezas syndrome caused by CUL4B gene mutations in two unrelated Chinese boys - Lin, Li; Yang, Qi; Zhang, Shujie; Zhou, Xunzhao; Li, Xiaoling; Yi, Sheng; Zhang, Qiang; Yi, Shang; He, Sheng; Qin, Zailong; Luo, Jingsi (Frontiers in Neuroscience, 2025)
As a component of the ubiquitin ligase complex, Cullin 4B (CUL4B) is involved in the process of ubiquitination of different substrates, controlling genome stability, nucleotide excision repair, and chromatin-remodeling. The mutations in the CUL4B gene are revealed to be a cause of Cabezas syndrome (OMIM 300354), a rare syndromic form of X-linked intellectual disability (XLID). In this study, whole-exome sequencing analysis and Sanger sequencing identified two maternally inherited likely pathogenetic variants (CUL4B, NM_001079872.2: c.803dupT/p. Leu268fs*5; c.953_957delTTATA/p. Ile318fs*2) in two probands, respectively. Patients carrying CUL4B variants presented with broad and variable phenotypic defects. The clinical manifestations of the two boys are consistent with Cabezas syndrome; however, they exhibit significant heterogeneity compared to previously reported cases. Phenotypic manifestations resulting from genetic variations may exhibit population differences and, in some cases, may present with concealed or latent expressions. Therefore, regular pediatric health check-ups and appropriate molecular diagnostic techniques are essential for the early detection, diagnosis, and treatment of such disorders. Our findings could be used to better define the genetic map in this area and will be valuable in the genetic diagnosis of the disease.